Modelling the nexus of carbon dioxide emissions, economic growth, electricity production and consumption: Assessing the evidence from Pakistan - Ali, Sajjad; Ghimire, Amogh; Khan, Adnan; Tariq, Gulzara; Shah, Ashfaq Ahmad; Tariq, Muhammad Atiq Ur Rehman (Frontiers in Environmental Science, 2022)
The economy of Pakistan has constantly been plunged due to its severe electricity shortages over the last two decades and persistently faces challenges in revamping its electricity supply network. The purpose of this research was to assess the causal relationship between carbon dioxide emissions, combustible renewable and waste, electric power consumption, electricity production from coal, hydroelectric and natural gas sources, energy use and gross domestic product. The scope of this research included Pakistan's annual time series data from 1971 to 2014. Statistical analysis is required to determine the long-term and short-term correlations among all research factors, this study employed Autoregressive Distributed Lag (ARDL) bound testing. This research also conducted Augmented Dickey-Fuller (ADF), Phillips-Perron (PP) and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) tests to evaluate the stationarity existence among dependent variable and independent variables. The outcomes of the fully modified least squares (FMOLS), dynamic ordinary least square (DOLS) and canonical co-integrating regression (CCR) estimators showed that coefficients of EC, EPH and GDP all were a significantly positive relationship with CO2 emissions while the coefficients of CRW, EPC and EU were negatively significant, respectively. Furthermore, the outcomes from the short-run analysis revealed that the error correction term value was -0.8668, which indicates that from short-run to long-run equilibrium, the adjustment of the deviation of CO2 emission is by 86.68 percent annually. Moreover, the diagnostic results also demonstrated that the model employed in this research is stable and reliable. Pakistan country selected in this research work simply because the deficit of power and if environmental degradation continues unchecked, it will eventually affect economic growth and CO2 emissions of the state. The study's primary policy recommendation is that government energy policymakers in Pakistan who create the environment framework in should pursue conservative energy measures as such measures will not negatively impact economic growth.